Assistance of the Community of Gampong Kuala Langsa Through the Manufacturing of Batik and Utilizing Mangrove Waste Skin - Sembiring, Desi Pasca; Putri, Elisa; Fitriani, Marida (Altifani Journal: International Journal of Community Engagement, 2022)
The use of mangroves as natural dyes has the potential to reduce environmental pollution and provide beautiful motifs in addition to providing natural color nuances. This community service activity aims to form a fishing group for the Kuala Langsa coastal area to process mangrove skin waste into batik dyes. The problems faced by partners are: (1) Partners do not have knowledge and skills in utilizing mangrove skins as batik dyes; (2) There is a need for activities that can support the community's economy in the coastal area of Kuala Langsa. (3) There is no public knowledge in marketing the batik they produce. The team developed a number of solutions to help partners successfully introduce, develop and preserve batik culture, using mangrove skins, national cultural heritage and commodities to improve the family's economic standard. They are also given basic skills and training in making batik so that it has a pattern and a function and is sold at a higher price. Forms of activities that will be carried out in the form of socialization and training. The form of training provided is by accompanying partners starting from making batik dyes from mangrove skin waste, batik procedures, and marketing strategies. After participating in this community service activities, it is hoped that the Kuala Langsa fisherman group will have the expertise and skills in producing batik as Kuala Langsa's superior product.